The Effect of Nanoencapsulated Phaleria macrocarpa Fruits Extract in Drinking Water on Jejunal Histomorphology of Broiler Chickens - N. Ningsih; B. Ariyadi; N. D. Dono; Supadmo Supadmo; Zuprizal Zuprizal (Tropical Animal Science Journal, 2019)
The purpose of this study was to investigate the characteristics of nanoencapsulated Phaleria macrocarpa fruits extract (NEPM) in drinking water and its effect on microbial population and histomorphology in the jejunal wall of broiler chickens. A total number of 200 male broiler chicks were distributed into 5 treatments with 4 replicates (10 birds in each replicate). The experimental treatments were control diet (T0; negative control), diet with tetracycline (T1; positive control), diet with 2.5% of Phaleria macrocarpa fruits extract (T2), diet with 2.5% NEPM (T3), and diet with 5.0% NEPM (T4). The diet was yellow corn and soybean meal that contains 20.44% CP, 2917.47 kcal/kg ME, 0.84% Ca, and 0.51% Pav. Variables evaluated were characteristics of NEPM, growth performance, intestinal microbial population (lactic acid bacteria (LAB) and Salmonella sp.), and intestinal histomorphology (villus height, crypt depth, and villus height to crypt depth ratio (VH : CD)). Data were analyzed using ANOVA in a completely randomized design. Orthogonal contrast test were used to separate mean of data when p-value differ significantly. Results showed that the size of NEPM was 778 nm with spherical shape and positive charges with the zeta potentials of +26.5 mV. Supplementing 5% of NEPM did not affect broiler growth performance, Salmonella sp. or crypt depth, but increased (p<0.05) LAB, villi height, and VH:CD. It can be concluded that 5.0% of NEPM in the drinking water had positive effect on the jejunal histomorphology and increased population of LAB while Salmonella sp. was not detected on all treatments.